Crenças sobre ensino/aprendizagem no ensino instrumental de línguas - Diniz, Deize Fernandes (2012)
The beliefs that involve the language learning/teaching process are made up through experiences of each individual and they reflect the personal views about learning an FL. By assuming that each person has their particular beliefs, this work aims to verify if those may change from the type of education received. The information needed to perform this research was obtained through questionnaires, semi-structured interviews and observations in the classroom. We based the theoretical approach on Barcelos (2010; 2007; 2004a; 2004b; 2003; 2001; 1995), who work with beliefs. Ramos (2005) served as a basis on specific language learning and Vygotsky (2001; 1998; 1978) on the socio interactionism view of language. It is quali-quantitative research done with 76 students/professionals from the course Curso de Capacitação em Português Língua Estrangeira Instrumental para Agentes do Governo Uruguaio: Polícia Rodoviária, offered by the Centro de Ensino e Pesquisa de Línguas Estrangeiras Instrumentais (CEPESLI), from Federal University of Santa Maria. Some of the beliefs brought by the group were: being an adult does not interfere in FL learning; learning Portuguese is easy; it is possible to learn it without needing to study; a learning directed to the student s occupation is sufficient to communicate at work. After the identification and comparison of these beliefs and the data analysis it was possible to conclude that the beliefs of the students may change even at different extents from learning/teaching experiences with an intensive and communicative learning language approach.